2020
DOI: 10.3389/fnhum.2020.00327
|View full text |Cite
|
Sign up to set email alerts
|

Motor Functional Reorganization Is Triggered by Tumor Infiltration Into the Primary Motor Area and Repeated Surgery

Abstract: In patients with gliomas, motor deficits are not always observed, even though tumor cells infiltrate into the motor area. Currently, it is recognized that this phenomenon can occur through the neuroplasticity potential. The aim of this study is to investigate the characteristics of motor functional reorganization in gliomas. Out of 100 consecutive patients who underwent awake surgery, 29 patients were assessed as regards their motor function and were retrospectively explored to determine whether positive motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Moreover, it is unclear whether the same results can be obtained in the normal brain since slow-growing gliomas might lead to reorganization with the functional shift from original localization at the cortical level (Duffau, 2014 ). Although cortical reorganization for language and motor function in gliomas has been reported (Saito et al, 2016 ; Southwell et al, 2016 ; Nakajima et al, 2020 ), brain plasticity regarding higher brain function, such as basic emotion, is poorly understood. In support of our results, some previous reports revealed that the premotor and posterior parts of the prefrontal cortices are related to basic emotion in the normal brain (Diano et al, 2017 ; Uono et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is unclear whether the same results can be obtained in the normal brain since slow-growing gliomas might lead to reorganization with the functional shift from original localization at the cortical level (Duffau, 2014 ). Although cortical reorganization for language and motor function in gliomas has been reported (Saito et al, 2016 ; Southwell et al, 2016 ; Nakajima et al, 2020 ), brain plasticity regarding higher brain function, such as basic emotion, is poorly understood. In support of our results, some previous reports revealed that the premotor and posterior parts of the prefrontal cortices are related to basic emotion in the normal brain (Diano et al, 2017 ; Uono et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, the positive mapping sites were plotted on the corresponding original 3DT1-images for each patient using iPlan Stereotaxy 3.0 software (BrainLab), according to operative reports and intraoperative video records. The exact locations of the DES points were determined by considering their spatial relationships to various anatomical landmarks (the gyri, sulci, vessel, and midline), as previously described (Tate et al, 2014 ; Nakajima et al, 2020 ). Next, each positive mapping site of emotion recognition on the original MR images was transferred to normalized T1-images.…”
Section: Methodsmentioning
confidence: 99%
“…[51] Further evidence of plasticity of the motor cortical network came from patients with primary motor cortex tumors. [52] Using intraoperative stimulation mapping, Duffau and colleagues described functional reshaping of motor areas that occurred in the interval between two consecutive surgeries in a patient with left precentral WHO grade 2 oligodendroglioma. [37] Although the patient exhibited no motor neurological impairments, intraoperative electrical stimulation showed motor function within the tumor, which resulted in incomplete tumor resection during the first surgery.…”
Section: Network Levelmentioning
confidence: 99%
“…The procedure for identi cation of overlapping positive mapping points was the same as that described in previous reports (Nakajima et al 2020a). First, subcortical positive mapping points were plotted on postoperative 3D T1 MR images while referring to the operative ndings and intraoperative records with iPlan Cranial 3.0 software (BrainLab).…”
Section: Procedures For Identi Cation Of Overlapping Positive Mapping Pointsmentioning
confidence: 99%